Automatic Mathematical and Chronological Prediction in Smartphone Keyboard (International Journal of Engineering and Computer Science, 2017)
Artificial intelligence is the mechanism which makes human work very easy by making the devices to process from the perspective of a human being. Predictive text is a feature in smart phones, which runs on Operating Systems such as iOS, Android, Windows etc. This feature plays a major role in helping the individual to select the word that succeeds the current word of their text message or statement. In the proposed system, the concept of predictive mechanism is taken to the next level by predicting mathematical solutions and chronological data. Thus, the system automatically does the mathematical calculations in the middle of a chat, without making the user switch to the calculator application; and also finds chronological data such as date and day, without having to switch to the calendar application.